Development of high strength and lightweight aluminum alloy and stainless-steel embedded aluminum alloy through an indirect extrusion process - Ling, Kai Xiang (Nanyang Technological University, 2021)
Load bearing components such as fasteners are widely used in industries such as automotive and aerospace. As part of light weight strategy to improve fuel efficiency and to become environmentally friendlier, composite material is proposed to replace load bearing components such as fasteners. Additionally, in the automotive engine compartments where the operating temperature is high, magnesium components are not fastened by steel fasteners because of the large difference in thermal coefficient between magnesium and steel. Aluminium fasteners are utilized but they are not as strong as steel fasteners. In a bid to improve it strength and remain lightweight, aluminium-stainless steel composite is extruded. Extrusion of composite can be achieved by extruding particle reinforced billets, short-fibre reinforced billets or co-extrusion of fibre and homogenous billet. The cost of co-extrusion of composite and the required number of manufacturing steps is lower as compared to extruding particle reinforced billets or short-fibre reinforced billets. However, there are numerous challenges, starting from the size of the extrusion machine required to co-extrude, the positioning of fibre within the extrudate and ensuring full encapsulation between matrix and fibre. In this FYP, an indirect co-extrusion technology of composite is developed to extrude A6061 matrix and SS304 fibre. The diameter of fibre is varied between 2 mm and 4 mm. Squeeze casting is a hybrid metal forming process which solidifies metals under applied hydrostatic pressure. Squeeze casting reduces porosity and the number of entrapped gases during solidification. Hence, squeeze casted components has fine grains and shown to significantly improve mechanical properties over conventional castings methods. A7068 alloy has one of the highest mechanical properties in the entire aluminium alloy. In this FYP, a study is conducted on the effect of squeeze casting A7068 followed by indirect extrusion.